Foundations of Augmented Cognition 7th International Conference, AC 2013, Held as Part of HCI International 2013, Las Vegas, NV, USA, July 21-26, 2013. Proceedings - Schmorrow, Dylan D.; Fidopiastis, Cali M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 5th International Conference on Augmented Cognition, AC 2013, held as part of the 15th International Conference on Human-Computer Interaction, HCII 2013, held in Las Vegas, USA in July 2013, jointly with 12 other thematically similar conferences. The total of 1666 papers and 303 posters presented at the HCII 2013 conferences was carefully reviewed and selected from 5210 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers accepted for presentation thoroughly cover the entire field of human-computer interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. The total of 81 contributions was carefully reviewed and selected for inclusion in the AC proceedings. The papers are organized in the following topical sections: augmented cognition in training and education; team cognition; brain activity measurement; understanding and modeling cognition; cognitive load, stress and fatigue; applications of augmented cognition.
Augmented cognition in training and education -- Team cognition -- Brain activity measurement -- Understanding and modeling cognition -- Cognitive load, stress and fatigue -- Applications of augmented cognition.
Keywords: Computer science; Information storage and retrieval systems; Education; Computer Science; User Interfaces and Human Computer Interaction; Computers and Education; Computer Applications; Information Storage and Retrieval